2006
DOI: 10.1073/pnas.0603488103
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus in complex with the Fab fragment of a neutralizing monoclonal antibody

Abstract: Flaviviruses, such as West Nile virus (WNV), are significant human pathogens. The humoral immune response plays an important role in the control of flavivirus infection and disease. The structure of WNV complexed with the Fab fragment of the strongly neutralizing mAb E16 was determined to 14.5-Å resolution with cryoelectron microscopy. E16, an antibody with therapeutic potential, binds to domain III of the WNV envelope glycoprotein. Because of steric hindrance, Fab E16 binds to only 120 of the 180 possible bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 43 publications
10
122
0
Order By: Relevance
“…The density related to the variable domains of the Fab fragments was almost as strong as the density of the glycoprotein shell, indicating ∼90% occupancy of the 120 binding sites (87% for X1, 93% for X2). The density related to the constant regions of Fab CR4354 is only about 0.7-fold as strong as the variable region, suggesting flexibility of the elbow angle between variable and constant domains, as often observed with antibody structures (23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The density related to the variable domains of the Fab fragments was almost as strong as the density of the glycoprotein shell, indicating ∼90% occupancy of the 120 binding sites (87% for X1, 93% for X2). The density related to the constant regions of Fab CR4354 is only about 0.7-fold as strong as the variable region, suggesting flexibility of the elbow angle between variable and constant domains, as often observed with antibody structures (23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 55%
“…Initial manual placement of the E protein structure of mature WNV (27) into the WNV-CR4354 complex density suggested that the general arrangement of the E monomers in the complex was essentially the same as in mature flavivirions, indicating that Fab binding did not significantly change the conformation of the E proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 4 A shows a reconstructed cryo-EM model using the electron density map for E16 (38) along with a representative binding configuration from the simulation for E16. In the simulation, E16 shows 100% occupancy at A and B epitopes and 20% occupancy for epitope C, as a result of steric exclusion by neighboring bound Abs.…”
Section: Partial Occupancy and Heterogeneitymentioning
confidence: 99%
“…For example, Kaufmann et al (38) and Fibriansah et al (17) attribute the lack of binding of E16 to epitope C and of 1F4 to epitope B, respectively, to possible steric hindrance of neighboring E-proteins in those epitopes to Ab binding. Dejnirattisai et al (22) suggest that differences in epitope presentation between epitope B and epitopes A and C are responsible for the weaker Ab binding to epitope B in EDE2-A11.…”
Section: Partial Occupancy and Heterogeneitymentioning
confidence: 99%
“…Many studies have shown that mAb binding to ED3 is most efficient at blocking virus attachment to cells (7)(8)(9)(10), and recently it has been suggested that some anti-ED3 mAbs may also impair virus membrane fusion (11,12). We have previously determined using virological techniques that residue Thr-332 in ED3 is a major neutralization site of WNV (13,14) (Fig.…”
mentioning
confidence: 99%